Rethinking malaria: Governance lessons from other disease programs - Kelechi Ohiri; Ifeyinwa Aniebo; Oluwafunmilayo Akinlade (Public Library of Science (PLoS), 2022)
The global disruptions brought about by the COVID-19 pandemic as well as the stagnation of progress of global malaria elimination efforts have provided an opportunity to rethink several aspects of the global malaria program, including its governance at all levels, from the community to the nation and to the world. Approaching this issue requires an examination of the critical governance factors that affect malaria elimination as well as lessons that could be learned from the governance of other global health programs. The paper, therefore, first reviews malaria program governance challenges at the global, national, and sub-national levels. We then conducted a literature review of governance factors that affected four major global disease elimination programs; (1) the global smallpox eradication program; (2) polio eradication efforts (focus on Latin America); (3) the onchocerciasis eradication program; and (4) global COVID-19 pandemic control efforts. Based on this review, we identified eight comment governance themes that impact disease elimination programs. These include 1) International support and coordination; 2) Financing; 3) Data use for engagement and decision making, 4) Country ownership; 5) National program structure and management, 6) Community support/engagement; 7) Multisectoral engagement; and 8) Technology and innovation The paper then illustrates how these eight governance themes were factored in the four disease control programs, draws lessons and insights about the role of governance from these programs and outlines the implications for governance of malaria elimination efforts. The paper concludes by making recommendations for improving governance of malaria elimination programs and how the analyses of other global disease control programs can provide new ideas and inspiration for a more robust push towards malaria eradication.